2016
DOI: 10.3389/fphar.2016.00288
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Activity and the Potential Mechanism of the Flavonoid Rich Extract from Sophora tonkinensis Gagnep. in KK-Ay Mice

Abstract: This study investigated the active principles, hypoglycemic activity and potential mechanisms of the flavonoid rich extract from Sophora tonkinensis Gagnep. (ST-EtOAc) in KK-Ay diabetic mice. An off-line semipreparative liquid chromatography-nuclear magnetic resonance (LC-NMR) and liquid chromatography-ultraviolet-electrospray ionization mass spectrometry (LC-UV–ESIMS) protocol was performed to determine 13 flavonoids from ST-EtOAc. ST-EtOAc administrated orally to the KK-Ay mice significantly increased their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…This screening system has been established according to our previous study [21,22]. To be brief, in cellular GLUTs storage vesicles (GSV), IRAP and GLUT4 displayed a strong co-localization reported by many researchers [23,24].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This screening system has been established according to our previous study [21,22]. To be brief, in cellular GLUTs storage vesicles (GSV), IRAP and GLUT4 displayed a strong co-localization reported by many researchers [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction and western blotting analysis were performed according to our previous study [21,22]. Briefly, L6 cells were pre-incubated with different dosage of SMR (10, 20, 40 μg/mL) and insulin (10 nM) for 24 h before extracting proteins for western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical review on necklace pod ([NP], Sophora tomentosa, reveals the presence of alkaloids, polysaccharides, isoprenylated flavonoids, isoflavonones, flavones, flavonols, and their glycosides. Such compounds have been reported to have diverse bioactivities including antioxidant and immunoregulatory [6,8]. It was reported that the extracts of S. tonkinensis and Sophora flavescens significantly control the levels of insulin, through stimulation of glucose transporter 4 (GLUT-4) which is attenuated by AMP-activated protein kinase (AMPK) pathway while being non-toxic for mice [9].…”
Section: Introductionmentioning
confidence: 99%